Re-treatment of residual aneurysms after flow diversion: An experimental study. Issue 3 (June 2018) - Fahed, Robert; Darsaut, Tim E; Kotowski, Marc; Salazkin, Igor; Raymond, Jean
Aim: Flow diverters are increasingly used to treat aneurysms, but treatment is not always effective. The management of aneurysms that fail to occlude following flow diversion is problematic. We aimed to reproduce failures in an animal model and study re-treatment with additional flow diverters alone or with flow diverters and liquid embolic agent. Material and methods: Twenty wide-necked aneurysms were created at the carotid-lingual bifurcation in 10 dogs, and were treated with flow diverters 4–6 weeks later. Follow-up angiography was performed at three months. Suitable residual aneurysms were randomly allocated: re-treatment with flow diverters alone ( n  = 6), or with the injection of liquid embolic between two layers of flow diverters ( n  = 4) or no re-treatment ( n  = 2). Angiography was repeated three months later, followed by euthanasia, photography and pathology. Results: Patent wide-necked aneurysms were produced in 17/20 attempts (85%); three months after flow diversion there were 15/17 (88%) residual aneurysms. In three cases, re-treatment was not possible because the flow diverter had prolapsed into the aneurysm, leaving 12 aneurysms to study. Re-treated aneurysms showed improved angiographic results at six months (median score of 2; P  = 0.03), but residual aneurysms were present in all cases. Parent artery occlusion occurred in two aneurysms treated with flow diverter plus liquid embolic. At pathology, aneurysms were only partially filled with thrombus; leaks through the flow diverters were found in the neointima connecting the arterial lumen to residual aneurysms. Conclusion: Re-treatment of residual flow-diverted experimental aneurysms with additional flow diverters did not lead to aneurysm occlusion.